Rambo 3 [videorecording (DVD)]. - Macdonald, Peter, 1957-; Stallone, Sylvester; Crenna, Richard, 1927-2003 (Artisan Entertainment Inc., 2004)
Rambo battles Russians invading Afghanistan. Includes deleted scenes, audio commentary with Sylvester Stallone, and more.